Design of Lubuklinggau City Policy: A Review of the Establishment of Local Regulations on the Guidance and Development of Micro and Small Industries - Fauzan Aziman, Muhammad; Hakim, Kahar (Indonesian Association for Public Administration (IAPA), 2024)
This research examines the policy formulation process for establishing a Regional Regulation on the Guidance and Development of Micro and Small Industries in Lubuklinggau City. This initiative was taken by the Lubuklinggau City government in 2024 to address various challenges in industrial development in the city. Using qualitative methods with data collection techniques through focus group discussions, interviews, observations, and documentation studies, this research focuses on the seven initial stages of the policy formulation process. The results show that the Lubuklinggau City government has implemented a comprehensive approach, including Regulatory Impact Analysis (RIA) in decision-making. Findings revealed a change in policy focus to micro and small industries and stakeholder engagement through public consultation. The analysis also revealed plans to establish an industrial centre area and develop an integrated information system for the data collection on micro and small industries. The resulting policy design combines aspects of guidance and development, including training programs, mentoring, and strategies for developing industrial infrastructure and resources. Based on these findings, the research recommends further studies that include policy implementation and evaluation stages to understand this policy's long-term impact and effectiveness in supporting the growth of micro and small industries in Lubuklinggau City.